Rearticulating Islamic Feminism - Kabir, Gedong Maulana (Martabat: Jurnal Perempuan dan Anak, 2023)
This article explores the role and impact of the Indonesian Women Ulema Congress—Kongres Ulama Perempuan Indonesia (KUPI) in shaping the narrative of Islamic feminism and public policy regarding gender issues in Indonesia. This movement faces challenges from both cultural (patriarchal culture) and conservative religious views that reject the narrative of Islamic feminism. Nevertheless, the two occurrences of KUPI in 2017 and 2022 demonstrate that the impact of this movement is significant. This research uses content analysis methods to assess various types of publication material, including justice gender fatwas and official publications related to KUPI. The main research question is to what extent the theological and juridical approaches KUPI used in formulating gender fatwas influence public perceptions and policies in Indonesia. This article finds that the gender justice fatwa by KUPI not only impacts the social and cultural aspects but also shapes policy decisions, particularly in areas of anti-sexual violence, forced marriage, environmental, health, and religious violence. This article enriches the academic understanding of how Islamic feminism is articulated and implemented in a context with broad cultural and religious diversity and provides new insights into the dynamics of Islamic feminism at the global level through a contemporary case study in Indonesia.